State and Public Land Management: Issues of Encroachment and Protection Technique - Manandhar, Sanjaya; Joshi, Janak Raj; Ghimire, Subash (Journal on Geoinformatics, Nepal, 2017)
The aspect of the management of state and public land directly supports to alleviating poverty, food sovereignty, protection of human rights and peace and security. So, management of state and public land directly or indirectly touches security of common property rights, pro poor and indigenous access to land and revenue generation for the state. State and public land are normally badly managed throughout the world because of its low national priority agenda and insufficient policy process, institutional arrangement and information aspects. This paper assumes that, overall framework about policy, management and operational levels with external factors and review process of state land will enable for screening major concerns of reforming the regulatory framework, regularization of public land, complementary governance support, management rules for public property, improvement of institutional arrangements, data and information, users services, capacity building and user satisfaction. SWOT analysis has been performed to identify major factors of encroachment and strategies formulation for cases of protection technique. Badly managed state land and low priority agenda is not only decreasing its efficiency but increasing encroachment options too. Mainly the unclear definition of state and public land tenure, lack of proper land governance, having gap and overlaps in institutional arrangement and lack of information are causes of inefficient management of state land, which lead not only misuse and bad allocation of land but highly motivate to lead towards severe encroachments.